2014
DOI: 10.1016/j.nbd.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and cortical disinhibition in mice with restricted expression of mutant huntingtin to parvalbumin-positive cells

Abstract: Recent evidence suggests that interneurons are involved in the pathophysiology of Huntington Disease (HD). Abnormalities in the function of interneurons expressing the calcium buffer parvalbumin (PV) have been observed in multiple mouse models of HD, although it is not clear how PV-positive interneuron dysfunction contributes to behavioral and synaptic deficits. Here, we use the cre-lox system to drive expression of mutant huntingtin (mthtt) in parvalbumin (PV)-positive neurons and find that mutant mice exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
(67 reference statements)
0
11
1
Order By: Relevance
“…PV INs develop mHTT inclusion bodies and show electrophysiological changes in HD mouse models (Meade et al, 2002;Spampanato et al, 2008). Selective expression of mHTT in this IN population results in specific HD-related phenotypes, including impaired cortical inhibition (Dougherty et al, 2014). It should, however, be noted that our results do not exclude a possible involvement of other IN subtypes in the cortical HD pathology.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…PV INs develop mHTT inclusion bodies and show electrophysiological changes in HD mouse models (Meade et al, 2002;Spampanato et al, 2008). Selective expression of mHTT in this IN population results in specific HD-related phenotypes, including impaired cortical inhibition (Dougherty et al, 2014). It should, however, be noted that our results do not exclude a possible involvement of other IN subtypes in the cortical HD pathology.…”
Section: Discussioncontrasting
confidence: 59%
“…Reductions in certain populations of INs were detected in human postmortem HD brains (Kim et al, 2014;Mehrabi et al, 2016). Furthermore, studies in conditional mouse models demonstrated the importance of mHTT expression in INs for the development of cortical pathology and behavioral defects (Gu et al, 2005), and attributed certain electrophysiological and behavioral alterations specifically to IN dysfunction (Dougherty et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PV‐expressing interneurons play a role in movement control as their inhibition (Gittis et al, ) or selective expression of mHtt (Dougherty et al, ) is sufficient to generate a hyperkinetic phenotype in mice. Interestingly, previous studies in R6/2 mice have observed higher levels of mHtt neuronal intranuclear inclusions in PV‐expressing interneurons compared to NOS/SOM‐expressing interneurons (Kosinski et al, ; Meade et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patch-clamp recording shows deficits in GABAergic inhibitory transmission in frontal cortex of these mice (Ito et al, 2012). Early presymptomatic degeneration or dysfunction of interneurons has also been found in mouse models of amyotrophic lateral sclerosis (Martin and Chang, 2012) and Huntington’s disease (Dougherty et al, 2014). The disease within the cerebello-rubro-thalamo-cortical circuit in our tg mice possibly starts with the degeneration of hαSyn + Golgi cell interneurons in cerebellar cortex because we found these neurons degenerating in 1-month old mice.…”
Section: Discussionmentioning
confidence: 99%